2017
DOI: 10.5194/bg-14-145-2017
|View full text |Cite
|
Sign up to set email alerts
|

Transient dynamics of terrestrial carbon storage: mathematical foundation and its applications

Abstract: Abstract. Terrestrial ecosystems have absorbed roughly 30 % of anthropogenic CO 2 emissions over the past decades, but it is unclear whether this carbon (C) sink will endure into the future. Despite extensive modeling and experimental and observational studies, what fundamentally determines transient dynamics of terrestrial C storage under global change is still not very clear. Here we develop a new framework for understanding transient dynamics of terrestrial C storage through mathematical analysis and numeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
185
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(185 citation statements)
references
References 86 publications
(114 reference statements)
0
185
0
Order By: Relevance
“…Previous studies found that carbon input through aboveground litter to soil increased in the coniferous or mixed forests, but decreased in the broadleaved forest over the last three decades, while the soil carbon accumulation was greatest in the broadleaved forest among the three forests (Tang et al, ). This result contradicted the proportionality of soil carbon change with carbon input, which is used in most global land carbon models that use the first‐order kinetics of soil carbon dynamics (Luo et al, ). Furthermore, evidence showed that the old forests in both temperate and subtropical regions accumulated SOC at quite high rate (Carey et al, ; Luyssaert et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies found that carbon input through aboveground litter to soil increased in the coniferous or mixed forests, but decreased in the broadleaved forest over the last three decades, while the soil carbon accumulation was greatest in the broadleaved forest among the three forests (Tang et al, ). This result contradicted the proportionality of soil carbon change with carbon input, which is used in most global land carbon models that use the first‐order kinetics of soil carbon dynamics (Luo et al, ). Furthermore, evidence showed that the old forests in both temperate and subtropical regions accumulated SOC at quite high rate (Carey et al, ; Luyssaert et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Bolin () was one of the first to write a simple carbon cycle model in matrix form. However, this form of representing carbon models has become more common recently by the development of the dynamic disequilibrium (Luo & Weng, ), traceability framework (Xia et al, ), and the transient dynamics theory (Jiang et al, ; Luo et al, ) of the terrestrial carbon cycle. Within these frameworks, carbon stocks in ecosystem pools x are represented as dx(t)dt=x.(t)=U(t)·b+ξ(t)·A·K·x(t), x(t=0)=bold-italicx0, where x(t) is a vector of carbon pool sizes; U ( t ) is a scalar function that represents photosynthetically fixed carbon; b is a vector of partitioning coefficients of the photosynthetically fixed carbon to plant pools (e.g., leaf, root, and woody biomass).…”
Section: Carbon Cycle Models As Dynamical Systemsmentioning
confidence: 99%
“…By expressing models in this general and compact form, it is possible to better understand holistic behaviors of terrestrial carbon cycle models. For instance, the framework can be applied to better trace different components of the carbon cycle (Xia et al, ), determine timescales of different processes (Huang et al, ; Yan et al, ), determine the predictability and dynamic disequilibrium of the carbon cycle (Luo et al, ; Luo & Weng, ), and assess carbon storage capacity and potential (Jiang et al, ; Luo et al, ; Luo & Weng, ).…”
Section: Carbon Cycle Models As Dynamical Systemsmentioning
confidence: 99%
See 2 more Smart Citations